Mechanical, thermal and tribological properties of polyimide/nano-SiO2 composites synthesized using an in-situ polymerization - Zhao, Y.; Qi, X.; Dong, Yu; Ma, J.; Zhang, Q.; Song, L.; Yang, Y.; Yang, Q. (Pergamon, 2016)
Polyimide (PI)/nano-SiO2 composites were successfully fabricated via a novel in-situ polymerization. Microstructure, thermal properties, mechanical performance and tribological behaviors of these composites were investigated. The results indicate that nano-SiO2 dispersed homogeneously. Compared with pure PI, thermal stability and heat resistance are higher about 10 °C with the addition of 5 wt% nano-SiO2. Compressive strength and modulus of composite with 5 wt% nano-SiO2 increase by 42.6 and 45.2%, respectively. The coefficient of friction (COF) of composite with 5 wt% nano-SiO2 decrease by 6.8% owing to the thick and uniform transfer films. Excess nano-SiO2 could adversely affect the COF of PI/nano-SiO2 composite. Additionally, wear resistance deteriorates obviously since transfer film exfoliates easily and nano-SiO2 aggregates on the surface of transfer films.